Fitness Features Involved in the Biocontrol Interaction of Pseudomonas chlororaphis With Host Plants: The Case Study of PcPCL1606 - Arrebola, Eva; Tienda, Sandra; Vida, Carmen; de Vicente, Antonio; Cazorla, Francisco M. (Frontiers in Microbiology, 2019)
The goal of this mini review is to summarize the relevant contribution of some beneficial traits to the behavior of the specie Pseudomonas chlororaphis, and using that information, to give a practical point of view using the model biocontrol strain P. chlororaphis PCL1606 (PcPCL1606). Among the group of plant-beneficial rhizobacteria, P. chlororaphis has emerged as a plant- and soil-related bacterium that is mainly known because of its biological control of phytopathogenic fungi. Many traits have been reported to be crucial during the multitrophic interaction involving the plant, the fungal pathogen and the soil environment. To explore the different biocontrol-related traits, the biocontrol rhizobacterium PcPCL1606 has been used as a model in recent studies. This bacterium is antagonistic to many phytopathogenic fungi and displays effective biocontrol against fungal phytopathogens. Antagonistic and biocontrol activities are directly related to the production of the compound 2-hexyl, 5-propyl resorcinol (HPR), despite the production of other antifungal compounds. Furthermore, PcPCL1606 has displayed additional traits regarding its fitness in soil and plant root environments such as soil survival, efficient plant root colonization, cell-to-cell interaction or promotion of plant growth.